Nutrient distribution in flowering stems, nutrient removal and fertilization of three proteaceae cultivars - Hernández, MM; Fernández-Falcón, M; Álvarez, CE (International Journal of Agricultural Research, Innovation and Technology, 2014)
Several parameters of flowering stems of two cultivars of protea Leucospermum cordifolium (Knight) Fourc (Succession II and Tango) and one of protea Protea L. (Protea susannae x magnifica Susara) were studied in different commercial plantations. These included length and weight measures, nutrient concentrations of detached parts (flower heads, leaves and stems), and removal of nutrients of harvested flowers. A base for fertilization was also calculated. Harvested flowers of Susara removed more P, K and Cu than Succession II and Tango, and more Ca and Fe than Tango. Succession II showed the highest Zn removal. The P and Cu removal by the crop of Susara were significantly higher than those of both Leucospermum cultivars, while K, Ca, and Fe outputs of Susara exceeded only those of Tango. The nutrient top removals amounted to 4.55 g m-2 of N, 0.48 g m-2 of P, and 5.26 g m-2 of K. Data as a base to supply fertilizer to each cultivar are given, with N:P:K ratios of 1:0.08:0.87 for Succession II, 1:0.08:0.83 for Tango and 1:0.10:1.27 for Susara. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.21094 Int. J. Agril. Res. Innov. & Tech. 4 (1): 64-69, June, 2014